2007
DOI: 10.1007/s10654-007-9177-3
|View full text |Cite
|
Sign up to set email alerts
|

Commuting physical activity is favourably associated with biological risk factors for cardiovascular disease

Abstract: Commuting physical activity, independent of leisure time physical activity, was associated with a healthier level of most of the cardiovascular risk factors. An increase in commuting physical activity in the population may therefore reduce the incidence of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 38 publications
2
54
0
1
Order By: Relevance
“…Therefore, some individuals might prefer activities that can be incorporated into daily living activities. Physical activity in transportation to and from work could be such an activity for some individuals, as some might find it less time-consuming and more convenient to be physically active during commuting than at leisure time [11]. We have shown that increased commuting and leisure-time physical activity in the population is likely to have a positive impact on the prevention of diabetes.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, some individuals might prefer activities that can be incorporated into daily living activities. Physical activity in transportation to and from work could be such an activity for some individuals, as some might find it less time-consuming and more convenient to be physically active during commuting than at leisure time [11]. We have shown that increased commuting and leisure-time physical activity in the population is likely to have a positive impact on the prevention of diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Commuting and leisure-time physical activity are inversely associated with BMI in the Inter99 Study [11], and prospective studies have shown that physical activity can reduce the risk of diabetes independently of BMI or other measures of overweight/obesity [5,6,[37][38][39][40]. However, physical activity may also reduce total body fat and/or its distribution and facilitate weight maintenance, which indirectly reduces the risk of diabetes [35,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations